Laparoscopic fluorescence image-guided photothermal therapy enhances cancer diagnosis and treatment - Singh,M; Nabavi,E; Zhou,Y; Gallina,ME; Zhao,H; Ruenraroengsak,P; Porter,AE; Ma,D; Cass,AEG; Hanna,GB; Elson,DS (Nanotheranostics, 2019)
Endoscopy is the gold standard investigation in the diagnosis of gastrointestinal cancers and the management of early and pre-malignant lesions either by resection or ablation. Recently gold nanoparticles have shown promise in cancer diagnosis and therapeutics (theranostics). The combination of multifunctional gold nanoparticles with near infrared fluorescence endoscopy for accurate mapping of early or pre-malignant lesions can potentially enhance diagnostic efficiency while precisely directing endoscopic near infrared photothermal therapy for established cancers. The integration of endoscopy with near infrared fluorescence imaging and photothermal therapy was aided by the accumulation of our multifunctionalized PEG-GNR-Cy5.5-anti-EGFR-antibody gold nanorods within gastrointestinal tumor xenografts in BALB/c mice. Control mice (with tumors) received either gold nanorods or photothermal therapy, while study mice received both treatment modalities. Local (tumor-centric) and systemic effects were examined for 30 days. Clear endoscopic near infrared fluorescence signals were observed emanating specifically from tumor sites and these corresponded precisely to the tumor margins. Endoscopic fluorescence-guided near infrared photothermal therapy successfully induced tumor ablations in all 20 mice studied, with complete histological clearance and minimal collateral damage. Multi-source analysis from histology, electron microscopy, mass spectrometry, blood, clinical evaluation, psychosocial and weight monitoring demonstrated the inherent safety of this technology. The combination of this innovative nanotechnology with gold standard clinical practice will be of value in enhancing the early optical detection of gastrointestinal cancers and a useful adjunct for its therapy.